Report of Euseius consors (Acari: Phytoseiidae) on avocado trees of Michoacan, Mexico - Ramos Lima, Mayra; Ayala-Ortega, José de Jesús; Lara-Chávez, Ma Blanca Nieves; Vargas-Sandoval, Margarita (Revista Colombiana de Entomología, 2021)
To support the description of the diversity of Phytoseiidae mites and according to biological control, the mite Euseius consors is reported for Mexico. It was collected from avocado plants (Persea americana) in seven municipalities in the state of Michoacán, associated with Oligonychus persea (Acari: Tetranychidae), one of the most important pestmites in this crop. Hence, this scientific note is a contribution to the knowledge, the basis for the description of a potential biological control agent, and the ecosystem service that it can provide.